2007
DOI: 10.1017/s0029665107005666
|View full text |Cite
|
Sign up to set email alerts
|

Human milk: maternal dietary lipids and infant development

Abstract: Human milk provides all the dietary essential fatty acids, linoleic acid (LA; 18:2n-6) and α-linolenic acid (18:3n-3), as well as their longer-chain more-unsaturated metabolites, including arachidonic acid (20:4n-6) and DHA (22:6n-3) to support the growth and development of the breast-fed infant. Human milk levels of LA have increased in Westernized nations from mean levels (g/100 g total fatty acids) of 6 to 12–16 over the last century, paralleling the increase in dietary intake of LA-rich vegetable oils. DHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(182 citation statements)
references
References 56 publications
3
164
0
15
Order By: Relevance
“…However, since many dairy and meat products contain CLA [16], once the infant is weaned from infant formula, these known CLA-containing foods are common dietary components. A similar concern for the absence of 22:4 (n-6), an essential precursor to very long-chain (n-6) PUFAs needed for normal spermatogenesis and fertility [17], in any of the infant formulas may be forestalled in view of the presence of 20:4 (n-6), the precursor to 22:4 (n-6).A number of reports have shown that both 20:4 (n-6) and 22:6 (n-3) levels in human milk correlate positively with infant growth and development [18,19]. Our data indicate that the 20:4 (n-6) and 22:6 (n-3) mole % ranges for the human samples (0.22-0.59 and 0.054-0.29 respectively) are quite comparable to those found for the infant formulas (0.34-0.63 and 0.085-0.22 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, since many dairy and meat products contain CLA [16], once the infant is weaned from infant formula, these known CLA-containing foods are common dietary components. A similar concern for the absence of 22:4 (n-6), an essential precursor to very long-chain (n-6) PUFAs needed for normal spermatogenesis and fertility [17], in any of the infant formulas may be forestalled in view of the presence of 20:4 (n-6), the precursor to 22:4 (n-6).A number of reports have shown that both 20:4 (n-6) and 22:6 (n-3) levels in human milk correlate positively with infant growth and development [18,19]. Our data indicate that the 20:4 (n-6) and 22:6 (n-3) mole % ranges for the human samples (0.22-0.59 and 0.054-0.29 respectively) are quite comparable to those found for the infant formulas (0.34-0.63 and 0.085-0.22 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrients (e.g., minerals and vitamins), macronutrients (e.g., fatty acids), energy density (kcal/g), and volume have all been reported to vary, to some extent, among non-Western populations (Jelliffe and Jelliffe, 1978;Prentice and Prentice, 1995). Micronutrients and fatty acids may be wholly or partially derived from current maternal diets (Francois et al, 1998;Innis, 2007;Milligan, 2013;Stuetz et al, 2012;Yakes et al, 2011), although macronutrients appear moderately buffered from shortterm nutritional fluctuations because mothers can mobilize body reserves for milk synthesis during lactation (Prentice et al, 1981b;Villalpando and Del Prado, 1999). Unlike milk macronutrient composition, milk volume may be more sensitive to changes in maternal condition (Ettyang et al, 2005;Prentice et al, 1981b;Villalpando et al, 1992; but see also Pérez-Escamilla et al, 1995).…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
“…CLA (in particular cis-9, trans-11) in milk fat has been associated with anticarcinogenic effects, and is produced either as an intermediate during rumen biohydrogenation of linoleic acid (Harfoot and Hazlewood, 1997), or in the mammary gland by D9 desaturase from trans-11 C18:1 (vaccenic acid, VA; Mosley et al, 2006). n-3 PUFA have health-promoting effects (Boure, 2005;Innis, 2007). Increased commercial interest in adding value to milk and meat by increasing their nutritional qualities has stimulated research in nutritional manipulation of their FA profiles.…”
Section: Introductionmentioning
confidence: 99%